MEMBANGUN GENERASI EMAS: KETERAMPILAN DAN PENGETAHUAN SISWA MELALUI SBDP DI MIS AL-JIHAD - Ratna Rahayu Pertiwi; Istiyati Mahmudah (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2024)
The role of education is needed in moving towards a golden generation, especially in learning Arts, Culture and Crafts. Arts, Culture and Crafts (SBdP) is one of the learning content contained in thematic learning in elementary schools. This is important to do to prepare the younger generation to be superior and competitive. The aim of this research is to build students' skills and knowledge through SBdP learning by improving 21st century skills such as critical thinking, creativity, communication and collaboration. This research uses qualitative methods. Data collected through observation, interviews and documentation